Neural Circuits for Elementary Motion Detection. (December 2014) - Borst, Alexander
Abstract Detecting the direction of image motion is a fundamental component of visual computation and is essential for survival of the animal. However, at the level of the photoreceptors, the direction in which the image is shifting locally is not explicitly represented. Rather, directional motion information needs to be extracted from the photoreceptor array by comparing the signals of neighboring photoreceptors over time. The exact nature of this process as implemented in the Drosophila visual system is currently being studied in great detail, and much progress has recently been made in determining the neural circuits giving rise to directional motion information in this species.